Design and Numerical Simulation of Low-Fiber Hollow Spindle in Air-Jet Vortex Spinning - 张肖斌 薛文良 程隆棣 (东华大学学报（英文版）, 2015)
Based on the mechanical system of free-end fibers and the analysis of pulling free-end fibers out of the spun yarn during spinning,a low-fiber hollow spindle is designed and the air distribution of fluent field is simulated numerically. The negative pressure effect is much bigger at the top of low-fiber hollow spindle than that in Murata No.861,which is more conducive for single fiber to get into the channel of hollow spindle. The tangential velocity in 0-3 mm at the top of hollow spindle increases and the fluctuation of radial velocity is much stronger,which enhance the wrapping effect. In the addition,the distribution of axial velocity remains the same.